Pengaruh Hasil Belajar Siswa Terhadap Kinerja Prakerin Siswa Jurusan Akuntansi Di SMK Negeri 1 Bulukumba - M. Wahyu Ramadani Tanrajelling; M. Ridwan Tikollah; Fajriani Azis (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effect of learning outcomes on the performance of Prakerin students majoring in accounting at SMK Negeri 1 Bulukumba. The population in this study was all accounting students of SMK Negeri 1 Bulukumba totaling 153 students, while the sample in this study was taken using porposive sampling techniques, the sample from this study was 55 people. The data collection techniques used are questionnaires and documentation. The data analysis techniques used are descriptive analysis, instrument tests and hypothesis tests using SPSS 27 for windows. The results of this study show that, Learning outcome variables have a positive and significant effect on the performance of Prakerin students majoring in accounting at SMK Negeri 1 Bulukumba.